Sustainable Tourism Development Strategy for Area of Mina Mangrove Tunggulsari, Pati Regency: PESTLE Analysis Approach - Khayati, Afif Nur; Kusumantoro; Rachmadi, Moch Faizal (International Journal of Green Tourism Research and Applications, 2025)
Tourism development is directed at sustainable tourism by upholding the principles of economy, social and environment including in the tourist destination of Area of Mina Mangrove, Pati Regency, Central Java Province. However, there are several aspects of external conditions that affect tourism development such as global uncertainty. The urgency of this research is the need for an external condition analysis model in efforts to develop sustainable tourism in Area of Mina Mangrove which includes Political, Economic, Social, Technology, Legal and Environmental aspects known as PESTLE Analysis. Based on this, the purpose of the research is to identify and analyze the relevance of external conditions in the development of tourism in Area of Mina Mangrove, Pati Regency. This research method is a qualitative approach in mapping and analyzing data in a complex, continuous and integrated manner. The results of the study concluded that the Environment (E) aspect plays a very important role, because Area of Mina Mangrove is directly adjacent to the Java Sea. This is an opportunity, potential and challenge in itself which has a major impact on the environment and sustainable tourism ecosystem. Creating environmental innovation, research and development by mitigating the risks of challenges and packaging them into optimal tourism opportunities. Of course, working with various parties at the central and regional levels, including community involvement and groups/communities, companies and academics. Politic (P) also has a major contribution in developing tourism in the Area of Mina Mangrove.